The Effect of Local Revenue, General Allocation Fund, and Capital Expenditure Against Financial Performance - Putri Ramadhani; Rosmayanti; Alifa, Sarah; Pakulla’, Heriani; Minggu, Ayu Rinathi; Habbe, Abdul Hamid; Mediaty (AFEBI Accounting Review, 2023)
The purpose of this study is to examine and analyze the impact of local revenue distribution and capital expenditure general fund on the financial performance of South Sulawesi provincial government. This study is a quantitative study that uses statistical analysis to test research hypotheses. Using secondary data obtained from the 2019-2021 South Sulawesi Provincial Government Financial Statements the results of this study show that South Sulawesi Real Revenue and Capital Expenditure General Allocation Regional Fund has a positive impact on financial performance. The provincial governments local government financial performance is to use relevant key indicators to evaluate the local governments financial performance so as to help local governments understand their own financial situation and measure the achievements in achieving financial goals and public interests. Keywords: Financial Performance, Local Revenue, General Allocation Fund, and Capital Expenditure.